Analisis Uji Perbedaan Profitabilitas Sebelum dan Saat Terjadinya Konflik antara Israel dengan Palestina : Studi pada Perusahaan yang Berafiliasi dengan Israel Terdaftar di Bursa Efek Indonesia - Razi Zulmi; Maidar Maidar; Ermad Ermad (AKUNTANSI 45, 2025)
The Israeli conflict over its occupation of the Gaza Strip, Palestine is one of the phenomena of the Boycott, Divestment and Sanctions Movement. Then to find out whether this boycott has an impact or not, of course, we must investigate the ability of companies affiliated with Israel to generate profits. The purpose of this study is to determine whether there is a variation in profitability before and during the Israeli-Palestinian conflict for the period 2023-2024 with the profitability ratios used, namely return on assets, return on equity, and net profit margin. The method used in this research is quantitative, and the subject of this research is quarterly financial data of companies listed on the Indonesia Stock Exchange. With Eviews 13, data assessment techniques include Wilcoxon Signed Rank Test and Paired Sample T-Test. Using return on equity, return on assets, and net profit margin ratios for the years 2023-2024, the findings of this study show no significant difference in profitability before and after the Israeli-Palestinian war. The profitability levels of Israeli-affiliated businesses were similar, and Indonesian businesses were not significantly affected by the boycott.